Design of a fixed-pipe cold aerosol spraying system for chemical application in greenhouse - Wang, Shilin; Lu, Daipeng; Li, Xue; Lei, Xiaohui; Tang, Yuxin; Lyu, Xiaolan (International Journal of Agricultural and Biological Engineering, 2023)
Since the high temperature and humidity in a closed environment, pests and diseases are infecting and spreading seriously in greenhouses. However, the prevention and control of pests and diseases in greenhouses are still dominated by knapsack sprayers. For those reasons, based on twin-fluid atomization, droplet dispersion, and constant pressure transportation technique, a fixed-pipe cold aerosol spraying system composed of the control unit and the fixed-pipe spraying unit comes into being. The indoor pipeline execution unit of the spraying system could be interfaced with the liquid-supply or gas-supply equipment such as the liquid pump, air compressor, and tank of the outdoor master control unit through a quick coupling, which could realize the separation of operator and sprayer in hermetic greenhouse. The atomization of twin-fluid nozzle and the droplet deposition and distribution of the spraying system in greenhouse were tested. Results showed that about 70% of the particle size of the twin-fluid flow nozzle concentrated in the range of 32-65 μm under the spraying air pressure ranged from 0.2 MPa to 0.4 MPa. When the air pressure was 0.2 MPa, 0.3 MPa, and 0.4 MPa, the wind speed at the nozzle outlet reached supersonic speed, as the corresponding VMD of droplets were 45.6 μm, 43.2 μm, and 36.8 μm, respectively. The higher the air pressure is, the more uniform the spray deposition is in the greenhouse. When the air pressure was 0.2 MPa, 0.3 MPa, and 0.4 MPa, the CVs of the liquid deposition in the greenhouse were 109.1%, 62.6%, and 35.4%, respectively. The droplets produced by the spraying system will rapidly disperse into the whole greenhouse. The average deposition was 2.99 μL/cm2 in the front area of the nozzle, the deposition was 1.24 μL/cm2 in the area between two nozzles, and the deposition was 0.58 μL/cm2 in the area behind the nozzles. The spraying system is characterized by the distribution of spraying liquid throughout the entire greenhouse.Keywords: greenhouse, twin-fluid nozzle, spraying system, droplet spectra, distribution, depositionDOI: 10.25165/j.ijabe.20231601.6573Citation: Wang S L, Lu D P, Li X, Lei X H, Tang Y X, Lyu X L. Design of a fixed-pipe cold aerosol spraying system for chemical application in greenhouse. Int J Agric & Biol Eng, 2023; 16(1): 53–59.